Determinants of FinTech Use Behavior: The Role of Behavioral Intention and Government Support - Candy Candy; Doreen Angelina; Hesniati Hesniati (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the factors influencing Financial Technology (FinTech) use behavior among Generation Z in Indonesia by analyzing the role of behavioral intention as a mediator and government support as a moderator. Methodology: A quantitative approach was employed using a survey of 433 Generation Z FinTech users in Indonesia. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural-Equation Modeling (PLS-SEM) with SmartPLS. Results: The findings indicate that Attitude, trust, and privacy concerns significantly influenced behavioral intention. In addition, attitude, trust, and behavioral intention significantly affect use behavior, whereas privacy concerns do not directly influence use behavior. Behavioral intention also mediates the relationships between attitude, trust, privacy concerns, and use behavior. Interestingly, government support negatively moderates the relationship between behavioral intention and use behavior, suggesting that stronger external support systems may reduce the dependence of FinTech use on individual intentions alone. Conclusions: Behavioral intention plays an important role in translating psychological factors into actual use behavior. Meanwhile, government support shapes FinTech adoption through external, structural, and institutional support mechanisms. Limitations: This study is limited by the use of a survey method and a limited number of variables, which may not fully represent all factors influencing FinTech use behavior. Contributions: This study contributes to the development of technology acceptance research by integrating psychological and external factors into a single model. The findings also provide practical insights for policymakers and FinTech companies in improving digital financial service adoption among Generation Z.